Pelatihan Pembuatan Sabun Cuci Piring Berbahan Dasar Daun Pandan - Hariono, Tholib; Ashoumi, Hilyah; Syauqi, Ahsanu; Rosita, Dilla Fransisca; Amala, Karisma Wahyu; Mirda, Laila Rahma; Nugroho, Irkham; Prayogo, Rian Adi (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Geographically, Asemgede Village, Ngusikan Subdistrict, Jombang Regency, is located at the northernmost part of Jombang, directly bordering Lamongan Regency. Asemgede is a relatively new subdistrict, formed by the division of Kudu Subdistrict, based on Jombang Regency Regulation No. 15 of 2000. The village consists of one hamlet, two RW, and four RT. It is situated in a forested area between Jombang and Lamongan. The majority of its residents are farmers, pandan mat weavers, and charcoal artisans. The farmers in Asemgede Village apply a seasonal planting pattern, cultivating rice during the first planting season (October to March) and corn and tobacco in the second season (March to August). This highlights the village's potential for natural resource development, including the use of corn waste as a raw material for producing bio-briquettes or other products. With its abundant natural resources, Asemgede Village has the opportunity to develop organic material processing activities into economically valuable products. One example is the production of dishwashing soap made from pandan leaves (Pandanus amaryllifolius), which contain natural compounds such as flavonoids, alkaloids, tannins, polyphenols, and saponins, the latter acting as a natural biosurfactant. Saponins in pandan leaves can produce effective foam for cleaning and possess antibacterial properties. Compared to commercial dishwashing soap, pandan-leaf-based soap offers significant advantages, particularly the use of natural ingredients that are safer for skin health, free of harmful chemicals like triethanolamine, triclosan, preservatives, parabens, and SLS surfactants. This community development initiative seeks to empower Asemgede residents by providing training in making dishwashing soap from pandan leaves. The training aims to enhance the skills and knowledge of the village community in processing organic materials into valuable products, thereby improving their economic welfare. The initiative also focuses on increasing women's participation, especially members of the village's Family Welfare Movement (PKK), enabling them to contribute to the community's economic development and fostering innovation